Effectiveness of Public Service Delivery from One Window Service Office: A Comprehensive Review - Prak, Penh; Serey, Mardy; Hour, Chhunkry; Chem, Vuthy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2025)
One Window Service Office (OWSO) plays a crucial role in delivering essential public services to local residents. The OWSO, which located in all districts and municipal within the provinces, aims to facilitate efficient service provision by eliminating redundant procedures and ensuring that citizens receive timely assistance. The office integrates a wide range of administrative tasks, including business registration, land management, tax collection, and civil documentation, under a unified system designed to minimize bureaucratic hurdles. This review aims to explore the extent to which the OWSO in Cambodia has contributed to improved governance and enhanced citizen engagement. This study adopts a qualitative case study approach to examine the effectiveness of public service delivery at OWSO in districts and municipal of Cambodia. By focusing on the OWSO, the study provides a detailed understanding of institutional practices, challenges, and outcomes related to public service delivery. A comprehensive review of secondary data was conducted to gather information on the establishment, objectives, and implementation of the Bavet OWSO. As results, this review indicate that while the OWSO has successfully simplified administrative procedures and improved service accessibility, its effectiveness is hindered by inadequate staffing, limited technological integration, and inconsistent enforcement of standardized procedures. Comparative analyses with similar initiatives in Indonesia, the Philippines, and Vietnam reveal that more digitally advanced and institutionally supported OWSO models achieve higher levels of efficiency and user satisfaction. These comparisons underscore the importance of investing in digital infrastructure, strengthening institutional capacity, and implementing robust anti-corruption measures to maximize the benefits of one-stop service centers. Additionally, the review highlights the need for enhanced citizen engagement and service awareness to ensure that residents fully utilize the available services and contribute to continuous improvements in service delivery.